Adaptation problems of the post industrial heritage on the example of selected objects of Bydgoszcz = Problemy adaptacji dziedzictwa poprzemysłowego na przykładzie wybranych obiektów bydgoskich - Pszczółkowski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Post-industrial architecture was until recently regarded as devoid of value and importance due to obsolescence, but this awareness has been a clear change in recent years. The old factories become full-fledged cultural heritage, as evidenced by the inclusion of buildings and complexes of this type in the register of monuments and protected by their conservator. More and more often, therefore, one undertakes revitalization of degraded brownfield sites, and within these treatments - conversion works. Specific issues and problems related to the adaptation of industrial facilities are discussed in the article on the basis of selected examples, completed in recent years in Bydgoszcz.
Keywords: dziedzictwo poprzemysłowe; adaptacja; rewitalizacja; Bydgoszcz; postindustrial heritage; adaptation; revitalisation